The role of business leaders in information technology innovation in the new era of disruptive technology - Yusasniza Mohd Yunus; Aini Aman; Kamarul Baraini Keliwon (Penerbit Universiti Kebangsaan Malaysia, 2019)
The new era of disruptive technologies such as internet of things (IoT), robotic process automation (RPA) and virtual reality (VR) not only contributes to the growth of marketplaces but also changes the individuals’ experiences in using new technology. This study examines the role of business leaders in the new era of disruptive technology and how it can fundamentally change the organisations or individuals to adapt to work challenges in changing market dynamics across industries. The research questions include what are the role of business leaders in Information Technology (IT) innovation; what are the major challenges and how business leaders overcome the challenges. Based on data gathered through interviews among the business leaders with accounting background, the findings revealed that support from the business leaders is necessary to motivate and encourage IT users to innovate with new technology. However, resistant to change, feeling complacent and anxious towards new technology are some of the challenges that the business leaders have to deal with IT users. Business leaders believed that management involvement, continuous discussion, educating IT users, demonstration of knowledge and coaching will help to motivate and inspire IT users to make full use on the benefits of new technology. The contribution of the study are two folds. Theoretically, it promotes the new rival of theory or framework that goes beyond the traditional IT use. Practically, business leaders are open to new approaches, develop and gain support for team vision, implement and execute a strategy effectively.